An experimental analysis of assignment problems and economic rent dissipation in quota managed fisheries. (March 2015) - Emery, Timothy J.; Tisdell, John; Green, Bridget S.; Hartmann, Klaas; Gardner, Caleb; León, Rafael
Abstract: Assignment problems may remain in quota managed fisheries due to variation in the productivity of the stock across space and time. Unless fishers can agree to coordinate their fishing effort, they will compete amongst themselves and over-exploit the stock where or when the quota unit value is highest, leading to economic rent dissipation. Coordination may be made more difficult in a dynamic marine environment when groups are heterogeneous and cannot communicate amongst themselves. To investigate this supposition, a series of economic experiments were conducted using university students. Participants took on the role of either a quota owner or lease quota fisher and in the presence or absence of communication were asked to make individual harvesting decisions, which allowed researchers to assess the relative influence of these factors on group coordination. This study found that participants were more likely to make socially optimal decisions to prevent rent dissipation when they could communicate and were in an experimental group containing solely quota owners. Participants who were lease quota fishers were less likely to make socially optimal decisions due to: (i) inequality in wealth; (ii) insecurity of tenure; and (iii) asymmetric information exchange. As participants were aware of these disparities, it negatively affected the ability of heterogeneous groups to establish trust and a sense of identity, despite being able to communicate. While requiring further exposition in the field, these results provide a theoretical insight into the difficulties heterogeneous fishers may have in solving assignment problems in a dynamic environment. Highlights: Assignment problems in fisheries cause economic rent dissipation among harvesters. Experimental economics was used to assess how to prevent economic rent dissipation. The inability to communicate led to economic rent dissipation among harvesters. Communication improved coordination among harvesters. Heterogeneity among harvesters moderated the effect of communication.